2019
DOI: 10.21037/qims.2019.05.23
|View full text |Cite
|
Sign up to set email alerts
|

Cortical bone vessel identification and quantification on contrast-enhanced MR images

Abstract: Background: Cortical bone porosity is a major determinant of bone strength. Despite the biomechanical importance of cortical bone porosity, the biological drivers of cortical porosity are unknown. The content of cortical pore space can indicate pore expansion mechanisms; both of the primary components of pore space, vessels and adipocytes, have been implicated in pore expansion. Dynamic contrast-enhanced MRI (DCE-MRI) is widely used in vessel detection in cardiovascular studies, but has not been applied to vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Cortical porosity has a considerable influence on bone strength and is essential in fracture initiation and propagation [ 14 ]. Magnetic resonance imaging has linked increased cortical porosity to alterations of the tissue that occupies the pore space [ 43 ], including blood vessels. Accordingly, microvascular function has been linked to cortical porosity in patients with T2DM [ 44 •].…”
Section: Discussionmentioning
confidence: 99%
“…Cortical porosity has a considerable influence on bone strength and is essential in fracture initiation and propagation [ 14 ]. Magnetic resonance imaging has linked increased cortical porosity to alterations of the tissue that occupies the pore space [ 43 ], including blood vessels. Accordingly, microvascular function has been linked to cortical porosity in patients with T2DM [ 44 •].…”
Section: Discussionmentioning
confidence: 99%
“…Despite resolution limitations [42] intracortical vessels can be partly visualized in vivo in humans using clinical 3T MRI. A first feasibility study utilized DCE-MRI on a clinical 3T scanner to image intracortical vessels in the distal tibia of 19 volunteers (10 men, 9 women, mean age 63 ± 5 years) with low bone mass (T-scores -2.5 to -1.0) [33]. Using a vessel detection algorithm this study found a mean vessel volume of 0.032 mm 3 and a mean vessel density of 0.68 per mm 3 .…”
Section: Human Studies Of Intracortical Vesselsmentioning
confidence: 99%
“…2). Therefore, a multimodal imaging protocol was developed using a cortical pore mask derived from high-resolution peripheral quantitative CT to analyze vessels and perfusion in the cortical pore space using DCE-MRI [33]. The MRI protocol utilized a spoiled gradient echo sequences with circular cartesian undersampling reconstruction to increase temporal resolution to 30 s. This imaging technique was able to resolve vessels with a diameter larger than 200 mm in a virtual phantom study.…”
Section: Dynamic Contrast-enhanced Magnetic Resonance Imagingmentioning
confidence: 99%
“…2, 3, 4; e.g. Shea et al 2002;Wu et al 2019). Bone tissue vascular canal density characterizes bone physiology and growth.…”
Section: Osteological and Histological Proceduresmentioning
confidence: 99%
“…Because we were interested in mostly regional (sub-periosteal or outer cortical segment of bone) blood supply, we used a point count technique to investigate vessel 'occurrence' from which we estimated density per mm 2 (e.g. Prisby 2017; Shea et al 2002;Wu et al 2019;Viboolvorakul et al 2009). We targeted vessels that were longitudinal (i.e.…”
Section: Osteological and Histological Proceduresmentioning
confidence: 99%